2018
DOI: 10.1159/000490141
|View full text |Cite|
|
Sign up to set email alerts
|

Resveratrol Protects Murine Chondrogenic ATDC5 Cells Against LPS-Induced Inflammatory Injury Through Up-Regulating MiR-146b

Abstract: Background/Aims: Resveratrol (RSV) has been reported as a promising oral supplementation for osteoarthritis treatment, while the mechanism of its action is still unclear. The specific aim of this study is to decode one of the mechanisms by which RSV protects chondrocyte. Methods: Mouse chondrogenic cell line ATDC5 was treated with 30 µM RSV for 24 h, and 10 µg/ml LPS for 12 h, after which cell viability, apoptosis, and the release of pro-inflammatory cytokines were assessed. The expression of miR-146b in ATDC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…These data strongly indicate that the intra-articular injection of resveratrol significantly prevents the destruction of OA cartilage tissue through the stimulation of SIRT1, thus reducing the expression of HIF-2α and catabolic elements [138]. Recently, resveratrol has been found to exert anti-inflammatory activity in chondrocytes by upregulating miR-146b, thereby deactivating the NF-κB and p38MAPK signaling pathways [141]. The results of all these studies suggest that resveratrol actually acts as a multitargeting agent by modulating the inflammatory and apoptotic pathway in several steps.…”
Section: Resveratrolmentioning
confidence: 73%
See 1 more Smart Citation
“…These data strongly indicate that the intra-articular injection of resveratrol significantly prevents the destruction of OA cartilage tissue through the stimulation of SIRT1, thus reducing the expression of HIF-2α and catabolic elements [138]. Recently, resveratrol has been found to exert anti-inflammatory activity in chondrocytes by upregulating miR-146b, thereby deactivating the NF-κB and p38MAPK signaling pathways [141]. The results of all these studies suggest that resveratrol actually acts as a multitargeting agent by modulating the inflammatory and apoptotic pathway in several steps.…”
Section: Resveratrolmentioning
confidence: 73%
“…Jin [141] Mouse chondrogenic cells were treated with 30 µM resveratrol for 24 h and 10 µg/mL LPS for 12 h. Cell viability, apoptosis and the release of pro-inflammatory cytokines was assessed.…”
Section: In Vitro/porcine Chondrocytesmentioning
confidence: 99%
“…Zhang L et al found that miR-146b was down-regulated in chronic nonbacterial prostatitis and might be a effective target for patient treatment (24). Moreover, miR-146b participated in LPS-induced inflammation and apoptosis in murine chondrogenic ATDC5 cells (25). In our study, we displayed that miR-146b up-regulation attenuated pediatric pneumonia progression through facilitating cell viability, suppressing cell apoptosis, decreasing production of IL-6, TNF-α and IL-1β.…”
Section: Discussionmentioning
confidence: 56%
“…Chondrocytes were pre-seeded in 6-well plate and maintained with growth medium for overnight. LPS (Sigma-Aldrich, USA, 20 μg/ml) was added to the medium to induce OA-like inflammation response, as described previously [27]. In order to produce an early stage of inflammation, the chondrocytes were treated with LPS for 3 to 6 h, and produce a late stage of inflammation using a treatment for 24 or 48 h. As to the Glycyrrhizin treatment, its working concentration was 25 μM.…”
Section: Inflammation Of Chondrocytes Induced By Lpsmentioning
confidence: 99%